Aeroelastic Response of a Cable-Stayed Bridge Deck with Various Fairing Shape Models (Case Study of Suramadu Bridge) - H, I Gede Agung Shri Parta; Supriyadi, Bambang; Triwiyono, Andreas (Universitas Ibn Khaldun Bogor, 2025)
Aerodynamic phenomena poses risks for long-span cable-stayed bridge structures, nevertheless, the prevention method is often neglected on older bridges. The effort to reduce the risk and increase the aerodynamic performance of cable-stayed bridges mostly focuses on design and construction stages. This study attempts to improve aerodynamic performance by mitigating the aeroelastic heaving response of an existing bridge structure chosen as the subject, Suramadu Bridge. The approach is made by exploring different options applicable to already built bridges, such as the addition of fairings with varying shapes to modify the shape model of the bridge deck while maintaining the value of vertical and torsional stiffness. The study finds that there is relatively no increase in the lowest margin of critical vortex velocity of the bridge deck with fairing addition compared to the original bridge deck. The amplitude of oscillation caused by aerodynamic lift force is also fairly low since critical vortex velocity occurs in the range of 9.35-9.38 m/s. Upon increasing wind velocity up to the design wind speed of 37.8 m/s, there are significant differences in lift force and amplitude of oscillations. The shape model with the steepest fairing shows a significant decrease in amplitude, up to 35.6% lower than the original bridge deck, indicating a better aerodynamic stability. Meanwhile, the other two shape models show identical and higher amplitude compared to the original bridge deck.